Bilateral hemispheric alteration of memory processes in right medial temporal lobe epilepsy. Issue 5 (1st November 2002) - Dupont, S; Samson, Y; Van de Moortele, P-F; Samson, S; Poline, J-B; Hasboun, D; Le Bihan, D; Baulac, M
Abstract : Objective: Functional MRI (fMRI ) was used to investigate right medial temporal lobe epilepsy (RTLE) effects on verbal memory. Methods: BOLD fMRI data were collected from seven right sided MTLE patients (RTLE) and compared with the data previously acquired from seven left sided MTLE patients (LTLE) and 10 control subjects. Twenty two contiguous images covering the whole brain were acquired using an EPI echoplanar sequence. Subjects were instructed to learn a list of 17 words, and to recall it immediately and at 24 hours interval. Group analyses were performed using SPM96. Results: RTLE patients retrieval performances were significantly impaired as compared with the performance of control subjects. As compared with control subjects and LTLE patients, RTLE patients exhibited a different pattern of hemispheric activations and a global decrease in left hemisphere functional activity. Conclusion: MTLE cannot be considered as a model of pure well lateralised hippocampal dysfunction. The verbal memory impairment depicted in RTLE patients may be considered as the witness of a bilateral impairment of the neuroanatomical circuits subserving memory.